(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The influx of the covid-19 pandemic has an impact on all sides of human life, not least in the world of education especially in boarding schools. Each pesantren has its own policy. Many pesantren choose to repatriate their students. However, not a few pesantren who have a policy of continuing the learning wheel, one of them is in Pondok Pesantren As Salam Fathul Ulum Kwagean. Therefore, this research aims to find out the innovation of learning stategi in Pondok Pesantren As Salam Fathul Ulum Kwagean in the face of the covid-19 pandemic. The stages in the implementation process ranging from the presence of researchers to the location directly looking for data sources, interviews, observations, and documentation as a data collection step then analyzethedata to know how farlearning innovations applied in Pondok Pesantren As Salam Fathul Ulum Kwagean in the face of the covid-19 pandemic. There are several learning stratetgi inovaasi that are applied in Pondok As Salam Fathul Ulum Kwagean ranging from learning tahfidzul qur’an, kutubuts tsurats literacy (yellow book) and literacy of santri writings, newsletters and wall magazines. These efforts are carried out as a support for boarding school education and provide a space to think and process ideas and develop creativity and appreciation of students in the midst of the covid-19 pandemic era.